Influence of Online Hemodiafiltration on Hemoglobin Level, ESA-Dosage and Serum Albumin – A Retrospective, Multicenter Analysis - Winkler, Roland E.; Ahrenholz, Peter; Freivogel, Klaus (IntechOpen, 2011)
None